ORPHANED LEARNERS AND SCHOOL DROPOUT RATE IN PRIMARY SCHOOLS: THE CASE OF SHURUGWI DISTRICT, ZIMBABWE - Magwa, Simuforosa (Advances in Social Sciences Research Journal, 2017)
The number of orphans roaming in streets in Shurugwi urban continues to escalate rapidly and has not yet received adequate attention. The study sought to explore the challenges that that force orphans out of primary education into streets. The study adopted a qualitative approach using a case study design. Interviews, document analysis and focus group discussions were used to collect data from participants. It was found out that orphans have serious financial constraints that weaken their ability to stay in schools. Besides, orphans do not get psycho-social support necessary for school achievement. The study recommends for the provision of educational requirements to orphans, development of a special curriculum relevant to the needs of orphans and creation of a supportive environment that addresses the needs of orphans.